Amazonia 2040: Spatial‐explicit futures scenarios for the mosaic of protected areas in the Lower Rio Negro (MBRN), Brazil - Birmoser Ferreira‐Aulu, Marianna; da Fonseca; Marina Antongiovanni; de Araújo Bittencourt; Sissi Mikaella; Macuácua, Xadreque Vitorino; Zuquim, Gabriela (Wiley, 2026)
Amazonia faces a socio-environmental emergency driven by anthropogenic activities, leading to biodiversity loss and decay of ecosystem services. To address these effects, Brazilian initiatives have established a large-scale conservation approach known as the mosaics of protected areas (PAs), which fosters collaborative governance for conservation action. Practitioners face constant pressures from human activities and have historically endured intentional dismantling of governance, forcing the local leaders to become reactive and short-sighted. Long-term thinking can help governance anticipate change and better prepare for alternative futures.
We applied an innovative approach to futures workshops with the Council of Leaders of the Mosaic of Protected Areas of the Lower Rio Negro (MBRN), and the Federal University of Amazonas (UFAM). Participants co-created scenarios for the MBRN in 2040, negotiating desirable futures and aligning values and goals. The workshops were co-designed with stakeholders, incorporating futures literacy, leadership empowerment and spatial knowledge; building on a novel approach called spatial-explicit futures scenarios (SEFS).
Probable scenarios co-created in these workshops describe futures where local citizens have little agency in decision-making, depicting environmental decay, economic instability and high levels of corruption. In resistance, local associations strengthen through voluntary work and fight for the resilience of local governance despite the lack of resources.
Desirable scenarios point towards an ecologically respectful and sustainable MBRN, with effective governance of resources. In these scenarios, communities' interests are legitimately represented and play a fundamental role in decision-making. Young adults are professionally qualified, have implemented sewage systems, clean energy and integrated communication networks. Community-based tourism and the carbon-offset market strengthen the economy and well-being.
Practical implication. Improved preparedness of PAs managers and community leaders. Leadership processes are strengthened by anticipating challenges and co-creating actionable insights that make desired scenarios viable. Including historically silenced voices in territorial strategic planning opens up space for these groups to express their desires and aspirations and develop strategic plans. In doing so, SEFS promotes sustainable and just land-use planning. The proposed methodology contributes to decolonizing science and encourages inclusive, just and sustainable management. The method can be applied beyond Amazonia, enabling stakeholders to develop their own futures-thinking processes.